Frequency, Characteristics, and Correlates of Pain in a Pilot Study of Colorectal Cancer Survivors 1–10 Years Post‐Treatment. Issue 11 (6th September 2013) - Lowery, Amy E.; Starr, Tatiana; Dhingra, Lara K.; Rogak, Lauren; Hamrick‐Price, Julie R.; Farberov, Maria; Kirsh, Kenneth L.; Saltz, Leonard B.; Breitbart, William S.; Passik, Steven D.
Abstract Objective The long‐term effects of disease and treatment in colorectal cancer (CRC) survivors are poorly understood. This study examined the prevalence and characteristics of pain in a sample of CRC survivors up to 10 years post‐treatment. Design One hundred cancer‐free CRC survivors were randomly chosen from an institutional database and completed a telephone survey using the Brief Pain Inventory, Neuropathic Pain Questionnaire‐Short Form, Quality of Life Cancer Survivor Summary, Brief Zung Self‐Rating Depression Scale, Zung Self‐Rating Anxiety Scale, and Fear of Recurrence Questionnaire. Results Participants were primarily Caucasian (90%) married (69%) males (53.5%) with a mean age of 64.7 years. Chronic pain was reported in 23% of CRC survivors, with a mean moderate intensity rating (mean = 6.05, standard deviation = 2.66) on a 0–10 rating scale. Over one‐third (39%) of those with pain attributed it to their cancer or treatment. Chi‐square and t‐test analyses showed that survivors with pain were more likely to be female, have lower income, be more depressed and more anxious, and show a higher endorsement of suicidal ideation than CRC survivors without chronic pain. On average, pain moderately interfered with daily activity. Conclusions Chronic pain is likely a burdensome problem for a small but not inconsequential minority of CRC survivors requiring a biopsychosocial treatment approach to improve recognition and treatment. Open dialogue between clinicians and survivors about physical and emotional symptoms in long‐term follow‐up is highly recommended.